Big data and collection of information about the management and productivity in tobacco culture in the Campos Gerais Region - PR (Research, Society and Development, 2021)
Tobacco (Nicotina tabacum) is a crop that is present mainly in the southern region of the country, so it can be a good alternative for small producers in the countryside. With this, the accomplishment of a study through questionnaires shared by thirty producers of the Region of Campos Gerais, in the state of Paraná, they could present individually, through descriptive and multiple choice questions, to present their form of cultivation, to point out suggestions and also their main difficulties, such as fertilizing the soil. Thus, generating the possibility of creating ways to take information that is relevant to producers and that can somehow leverage their production, ensuring quality of service and also of product.